Mordomia e Liminaridade nas Festas do Mártir em Barroso - Rocha, João Azenha da (Trabalhos de Antropologia e Etnologia, 2020)
In the southern plateau of Serra do Barroso, where the Trás-os-Montes and Minho regions meet, different production methods as well as worshiping traditions associated with both agricultural and pastoral cycles flow together. The feasts in honor of São Sebastião that take place in this territory are intermingled with different factors that drive cyclical changes on certain aspects of the rituals constantly recreated. The changes take place, and have its roots in disagreements, in conflicts resulting from inequalities pervasive in all societies. The dynamics of change is a driver for a wealth of information, given that the periods of stability are feeble and fleeting. In this essay, we compare three places for the celebration of the Martyr, selected by its proximity and relevance, by revisiting other territories with feasts with the same invocation.